Some Fixed Point Theorems in Ordered G-Metric Spaces and Applications - W. Shatanawi (Abstract and Applied Analysis)
We study a number of fixed point results for the two weakly increasing mappings f and g with respect to partial ordering relation ⪯ in generalized metric spaces. An application to integral equation is given.